دراسة نسيجية-كيميائية مقارنة لنوعي الطيون Inula viscosa وInula graveolens المنتشرين في الساحل السوري - يوسف, عزيزة ابراهيم; منصور, أسامة (Latakia University Journal -Medical Sciences Series, 2013)
أجرينا في هذا البحث دراسة بيولوجية (مورفولوجية، بنى نسيجية، عناصر تشخيصية) وكيميائية كيفية (فحص دلالة ذاتية العقار وتحديدها، فصل المواد بالكروماتوغرافيا الطبقة الرقيقة) لنوعين من الطيون هما(L.) I.vis. وI. grav. (L.) المنتشرين في الساحل السوري، أظهرت نتائج الدراسة وجود الخصائص التالية : - نباتI.vis.، مُعمّر، أوراق رمحية مسننة، حجم وعدد النورات والأزهار أكبر، الثمرة أسطوانية متطاولة، وجود فراغات هوائية في الجذر، وجود ثلاث حزم وعائية ورقية، جدار حبات الطلع أقل سماكة، وقطر الثقب والكيس الهوائي أكبر، أوبار لامسة ذات قاعدة إجاصية وأقلّ طولاً، بنهاية مدببه. - نبات I. grav.، حولي، أوراق شريطية تامة الحواف، حجم وعدد النورات والأزهار أصغر، الثمرة (سبسلاء) بيضوية، لايوجد في الجذر فراغات هوائية، وجود حزمة وعائية ورقية واحدة، جدار حبات الطلع أكثر سماكة، وقطر الثقب والكيس الهوائي أصغر, أوبار لامسة ذات قاعدة شبه مغزلية وأكثر طواًل (أكبر)،بنهاية مدببه. - وجود القلويدات، الفلافونوئيدات، المواد العفصية عند النوعين، وجود اللاكتونات عند I. grav. فقط، ويُفسر ذلك وجود مواد فعالة ذات حلقة لاكتونية خماسية، والنتيجة السلبية عند I.vis. لاتعني عدم وجود اللاكتونات وإنّما عدم وجود لاكتونات خماسية الحلقة، كذلك عدم وجود سابونينات عند I.vis. ، وعند I. grav.. - أظهرت كروماتوغافيا الطبقة الرقيقة TLC في الشروط المستخدمة وجود (7) بقع عند I. viscose و(6) بقع عند I. grav. بـ RF مختلفة (3 بقع فقط مشتركة). - استطعنا إبراز الفوارق الشكلية والنسيجية والعناصر التشخيصية المميزة للنوعين فضلاً عن معرفة بعض المواد الفعّالة الموجودة بفحص الدلالة وتحديد الذاتية، وفصل هذه المواد على الطبقة الرقيقة، ويعتبر ذلك نواة لبحوث أخرى مكملة خاصةً في التحليل الكيميائي وأيضاً دراسة التأثير الحيوي لنوعي الطيون. In this research we studied the biological characters (morphology, tissue structures, diagnostic elements) and qualitative chemical particulars (identification tests and separation by TLC) for two species of inula (L.): I.viscosa and I.graveolens (L.) common in the Syrian coast. The study showed the following characteristics in the two species : - Plant I. viscosa, perennial; leaves spear crenate; size and number of inflorescences and flowers are smaller; fruit cylindrical elongated; the presence of air voids in the root; there is one vascular leafy bundle; the wall of pollen grains is thicker; and diameter hole and the air bag are larger; pollen with shorter pear-shaped base with a pointed end. - Plant I. graveolens, perennial; full-edged striped leaves; the size and the number of inflorescences and flowers are smaller; oval fruit; there are no aerial spaces in the root; there is one foliar vascular bundle; the wall of pollen grains is thicker, but the diameter of hole and the air bag is smaller; pollen with longer semi-spindle base and it is pointed by the end. - We noted the presence of alkaloids, flavonoids, tannins in the two species, the presence of lactones in I. graveolens only. We can explain this by the presence penta circle lactonic substances; the negative result with I. viscosa does not mean the absence of lactones, but it means that there are no penta -circle lactones; I. viscosa,and I graveolens. have no Saponins. - Thin layer chromatography (TLC) showed the presence of (7) spots in I. viscosa and (6) spots in I. graveolens with different RF (only 3 common spots). -We were able to highlight the differences of form, textile and diagnostic elements in the two species, in addition to identifying some substances by examining the identification tests, and the separation of the constituents by TLC. This study could be the starting point for other complement researches, especially in chemical analysis and biological tests.